RANCANG BANGUN SISTEM INFORMASI MANAJEMEN PENYEWAAN KENDARAAN BERMOTOR MODEL DARING - juni sasmiharti (LIAISON JOURNAL OF BEST, 2022)
Utilizing information technology in a business activity today is a must in order toremain competitive with similar companies. Vehicle rental companies can take advantage of thistechnological facility in business activities by creating a vehicle rental business managementinformation system. Vehicle rental companies that have not optimally utilized this technology mayrun the risk of losing transaction data and customer data. The loss of this important data can reducethe speed of service, thus affecting the company's performance. These deficiencies can result in thecompany's performance and unable to compete with similar companies that already utilizeinformation technology. These problems become the material of this research to build a computerizedvehicle rental data management information system. The information system built in this study wasbuilt so that it can operate online where customers can use it directly. The Vehicle RentalManagement Information System was built using PHP programming with a MySQL database usingthe waterfall methodology. The system built can provide convenience for vehicle rental companymanagers and customers because they can transact safely where data is stored in a computerdatabase.Keyword: Vehicle Rental, PHP Programming, Web, MySql